Design-based research as a guide for the construction of inquiry teaching learning sequences: scientific method and ecology in the classroom (Research, Society and Development, 2022)
This study constituted a design-based research that aimed to analyze the articulation of themes of relevance for the understanding of the epistemology of sciences in the perspective of Inquiry. The research was carried out in a federal school and involved 64 high school students in three cycles of application of an teaching learning sequence (TLS) that relates scientific method with ecology in a problem situation about agriculture. The TLS was designed, applied, evaluated, redesigned and reapplied in the remote teaching model. As a result, we found that the TLS had the potential to promote skills and abilities described in the National Common Curricular Base, contemplating the promotion of the scientific literacy of the participants. The evaluation of the TSL carried out by the students revealed the importance of scaffolds in remote teaching, as well as revealing difficulties related to social isolation. The positive results of the research suggest the application of this TLS in presential teaching, to assess its potential in the teaching-learning process without the variables of remote teaching.